Stridhanam: Rethinking Dowry, Inheritance and Women's Resistance among the Syrian Christians of Kerala - Philips, Amali (Anthropologica, 2022)
The property experiences of Syrian Christian women in Kerala, India, viewed in the contexts of their kinship positions (as daughters, sisters, wives, mothers and widows) and spatial arrangements in natal, conjugal and affinal house holds, provide a more nuanced understanding of dowry and inheritance practices than the decontextulized generalizations offered by the dominant theoretical paradigms. Depending on their kinship positions, the mutuality of kinship with men, the diverging interests of natal, affinal and conjugal households, the relative strengths of patriarchal hegemony and counter-hegemony and the accessibility to the secular legal system, women respond to property disputes by acquiescing, accommodating, bargaining or overtly resisting. These experiences, while questioning some of the paradigmatic explanations of Indian dowry, add a new dimension to the growing literature on women's resistance and help establish a much needed linkage between the study of dowry and that of women's resistance.